Оптический датчик температуры на основе нанокристаллической пленки SiC - Lopin, A. V.; Semenov, A. V.; Puzikov, V. M. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
An interference temperature sensor has been developed using nanocrystalline films of cubic silicon carbide deposited directly by ion flow onto a leucosapphire substrate. The optical properties and thermal sensitivity of the “nanocrystalline SiC film/leucosapphire” structures have been measured and analyzed.